Gregarious Flowering of Montane Bamboos Sinarundinarla falcata (Nees) Chao & Renv. and Schizostachyum fuchsianum (Gamble) Majumdar in Arunachal Pradesh, India - Naithani, H. B.; Biswas, S.A.S.; Chandra, Anup (Indian Forester, 2007)
No abstract